ANALISIS KESULITAN PEMBELAJARAN MATEMATIKA SISWA KELAS V SD NEGERI 012 BANGKINANG KOTA - Mufarizuddin Mufarizuddin (Departement of Mathematics Education, 2018)
This research is to find out the location of difficulty and the factors that cause difficulties in learning mathematics on the subject of integer count operation. Research subjects are taken that is class V which has the average value of mathematics still under Minimum Exhaustiveness Criteria (KKM). Data collection methods used were test method, observation method, interview method. The test method is used to obtain student completion data on the counting integer counting material in the form of essay 10 items. Observation method is used to determine the condition of subjects during the learning activities of mathematics and to know the factors that can affect the learning process of mathematics. Interview method is done to know clearly problem faced by student when study material counting integer. From the data of final analysis result, it is found that the percentage of students' difficulties in skill is 50% including enough category, difficulties in understanding the concept of 23.3% including less category and difficulty in problem solving by 20% including less category. So expect teachers in shaping the pattern of teaching mathematics is not solely shown in the students' skills in solving the problem. But more important is how to invite students to understand and understand and master the existing concepts well and correctly, so that students do not have difficulty in learning mathematic. Keywords: Analysis, Student Difficulties